Case report: A rare case of catastrophic Takayasu arteritis: acute ischemic stroke and anterior ischemic optic neuropathy - Olalusi, Oladotun V.; Yaria, Joseph; Makanjuola, Akintomiwa; Akinyemi, Rufus; Owolabi, Mayowa; Ogunniyi, Adesola (Frontiers in Stroke, 2024)
Acute ischemic stroke is a known complication of Takayasu arteritis (TAK) but infrequently the presenting feature. There is no report of concomitant acute ischemic stroke (AIS) and anterior ischemic optic neuropathy (AION) as an initial manifestation of TAK. We report a case of TAK causing stroke and painless vision loss in a young Nigerian female. A 33-year-old female presented with abrupt onset weakness in the right extremities and left-sided painless vision loss. History included joint pain, malaise, syncope, and dizziness with peripheral vascular collapse requiring recurrent hospital admissions. She had absent left radial, reduced left carotid pulses, and unrecordable BP in the left arm. There was a relative afferent pupillary defect (RAPD) with a fundoscopy finding of optic disc pallor. She had expressive aphasia, right facial paresis, and right flaccid hemiparesis. Brain computed tomography (CT) showed an infarct in the left middle cerebral artery (MCA) territory. The brain CT angiography showed diffuse enhancing aortic arch wall thickening and multiple aortic arch branch obstructive disease. The diagnosis was TAK complicated by left hemispheric infarctive stroke and left AION. She was commenced on prednisolone, azathioprine, and secondary stroke preventive care. Her vision improved to counting fingers, with good functional outcomes and reduced disease activity. This case highlights the challenging diagnostic trajectory of TAK in a Nigerian female and a unique multi-vessel affectation. Clinicians should be aware of the protean clinical presentations of TAK, to reduce adverse cardiovascular complications.